The ANALISIS TINGKAT KERUSAKAN JALAN METODE PCI PADA RUAS JALAN SUNGAI PINANG KABUPATEN BANYUASIN SUMSEL: ANALISIS TINGKAT KERUSAKAN JALAN METODE PCI PADA RUAS JALAN SUNGAI PINANG KABUPATEN BANYUASIN SUMSEL - Sazili Harnawansyah; Yusri Bermawi; M. Fauzy Ridwan; Andri Kurniawan (PILAR, 2022)
Transportation infrastructure is infrastructure prepared to support the transportation of people. Goods and services using certain transportation modes. Therefore we need an effective and efficient transportation service. One of the important land transportation infrastructures is the road. Road infrastructure that is burdened by high traffic volume and repeatedly causes the pavement layer to experience a decrease in service levels. One of the roads that had decreased and became the object of the chosen research location, namely sungai pinang, banyuasin regency from sta 9+400 – 11+700 due to damage to several road components that hampered the smooth transportation of traffic. This study aims to determine the types and levels of road damage and the value of road pavement conditions so as to determine how to handle them. The method used in this research is the Pavement Condition Index (PCI) method. Where from these methods, after analyzing there are types and levels of road damage, namely Aligator Cracking 1,009%, Block Cracking 0,18%, Crack & Decrease 0,4 %, Depression 1,036%, Edge Crack 0,109%, Long Crack & Transverse Crack 0,837%, Hole 0,48%, Slip Cracking 0,032% and Weathering/Removing Grain 0,038%. Then also obtained an average PCI value of 65,8 in the moderate category (fair) which means it needs to be said that the Structual Improvemen.